Perspectives in Support of the Narrative Turn in Pastoral Care - Müller, BA; Müller, J (Nederduitse Gereformeerde Teologiese Tydskrif, 2006)
Liturgy as an agent in transformation processes This article is in principle a practical-theological argument for a liturgical praxis which can act as a revisioning agent in processes of transformation. It stresses the important role of the litrugy in the creation and nourishment of faith-experiences as the source of renewed energy in such processes. In the liturgy new creative spaces must be developed where a new moral order and moral practices can be (re)learned. Through the formation of such new lifeworlds the litrugy can give redescriptions of hte so-called unchangeable realities in society. In the article the litrugical sources of energy is described in terms of hte experience of the praesentia dei realis, the histroy of salvation made relevant through litrugy, the subversive power of liturgy, its didactical value, the humnic forces, the role of confession, the role of services in ecumencial contexts and the creation of new forms of litrugical celebration.